Rosalie Favell : longing and Not Belonging - Rice, Ryan; Ace, Barry (CV Photo)

(untitled) (Les Productions Ciel variable, 2000)
Longing and Not Belonging is an exhibition of 41 digital-output works by photographer Rosalie Favell. Favell has chosen to explore her identity as a mixed-blood urban Cree through her family photographs and images of twentieth-century pop culture. Her family photographs remind us of our own special times and provide documentation for her history. Her work takes us to places not uncommon to our own life experiences. The images tell us, and others, who we are and where we came from, and they can even provide us with insight into where we are going.